2014
DOI: 10.1021/jp5074957
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Silver Nanoparticles within an Aqueous Dispersion of Nanosized Zeolite Y: Mechanism and Applications

Abstract: Stable aqueous dispersion of silver ion-exchanged nanozeolite Y was reacted with the three common dihydroxyphenols, hydroquinone, catechol and resorcinol. With hydroquinone and catechol, there was rapid reduction of the intrazeolitic silver to form metallic silver with complete destruction of the zeolite framework. Resorcinol, the weakest reducing agent amongst the group behaved differently. The formation of metallic silver was considerably slower, and the zeolite framework was mostly intact. This made it poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 69 publications
1
20
0
Order By: Relevance
“…Besides, recent progress in this context further supported the importance of such a reaction in the evaluation of catalytic activity of silver nanoparticles, which showed great potential for practical application in water treatment. 15 Poly(ethylene oxide propylphosphonamidate) (PEOPPA)-supported nanosilvers, 16 metal-organic framework-based silver nanoparticles, 17 semi-IPN hydrogel-based silver nanoparticles, 18 bimetallic gold/silver core-shell nanoparticles or other Ag-based bimetallic nanoparticles, 19 zeolite Y-dispersed silver nanoparticles, 20 silver/reduced graphene oxide or N-doped graphene hybrid nanocomposites, 21 superparamagnetic silver/halloysite nanotube/Fe 3 O 4 nanocomposites, 22 silver nanoparticles supported on polymer material, 23 etc., have been designed and prepared for the reduction of 4-nitrophenol, which happens to be a hot topic for nanocatalysis. However, most of the research studies for this reaction only deal with the simple examination of various silver nanoparticles that supported various types of inorganic or organic supports.…”
Section: Reduction Of Nitroaromaticsmentioning
confidence: 99%
“…Besides, recent progress in this context further supported the importance of such a reaction in the evaluation of catalytic activity of silver nanoparticles, which showed great potential for practical application in water treatment. 15 Poly(ethylene oxide propylphosphonamidate) (PEOPPA)-supported nanosilvers, 16 metal-organic framework-based silver nanoparticles, 17 semi-IPN hydrogel-based silver nanoparticles, 18 bimetallic gold/silver core-shell nanoparticles or other Ag-based bimetallic nanoparticles, 19 zeolite Y-dispersed silver nanoparticles, 20 silver/reduced graphene oxide or N-doped graphene hybrid nanocomposites, 21 superparamagnetic silver/halloysite nanotube/Fe 3 O 4 nanocomposites, 22 silver nanoparticles supported on polymer material, 23 etc., have been designed and prepared for the reduction of 4-nitrophenol, which happens to be a hot topic for nanocatalysis. However, most of the research studies for this reaction only deal with the simple examination of various silver nanoparticles that supported various types of inorganic or organic supports.…”
Section: Reduction Of Nitroaromaticsmentioning
confidence: 99%
“…The instability of the nanometer-sized silver particles due to their tendency to migrate and aggregate irreversibly into larger nanoparticles is, however, a recurrent problem. The use of confining scaffolds, such as zeolite-type material, is often reported in the literature as an efficient solution to overcome particle migration at the surface and eventually grows, leading to a loss of performances [18,19]. Nevertheless, over the course of a pilot-scale study of the TSA process on site, we observed a drop in adsorption capacity that was concomitant with the appearance of AgCl and an apparent growth of silver nanoparticles at the zeolite surface.The objectives of this study are (i) to determine why xenon adsorption capacity decreases, with a special focus on understanding the origin and role of Cl; (ii) to study regeneration parameters that can restore the adsorption capacity; and (iii) to validate the regeneration process in the context of a cyclic TSA process in relevant conditions.…”
mentioning
confidence: 69%
“…Zeolite Y particles of roughly two sizes, 200 nm and 40 nm, were synthesized. The procedures used to prepare and characterize these particles are detailed in the recent dissertation work conducted at The Ohio State University [39] and in the related publication [40]. The synthesis of smaller zeolite particles of roughly 40 nm size was based on prior work by Holmberg et al [41].…”
Section: Methodsmentioning
confidence: 99%